(untitled) (Revista de Ciências Agroveterinárias, 2013)
This study aimed at quali-quantitatively characterizing the urban trees in the city center of Lages, SC. Thirty two roads were sampled for this purpose, where all trees with CBH (circumference at breast height, measured at height of 1.30 m) equal or longer than 15 cm were identified, measured and evaluated. The species were classified as native of Lages region or exotic. The Pielou evenness (J) and Shannon-Wiener (H’) indexes were calculated. The results showed that only 37.5% of the roads (12) presented trees, where a total of 149 individuals belonging to 13 species were inventoried. From all species found, only three (23.08%) were native from Lages region, while 10 were classified as exotic (76.92%). There was an irregular distribution of individuals per species, resulting in an elevated dominance (J = 0.49) with a great abundance mainly of Ligustrum lucidum W.T. Aiton. The large percentage of this species in relation to the small amount of species planted contributes to the small diversity of the arborization (H’ = 1.25). Most species are large in size, which may consequently cause interference in urban elements in the future. At the time of assessment, 6.04% of the trees interfered with the pedestrian transit, 0.67% with buildings’ walls, 8.05% with electric wires and 28.86% with sidewalks. The use of inappropriate species for urban road environments contributes to this pattern.